Improving the microstructures and mechanical properties with nano-Al2O3 treated wire in underwater submerged arc welding. (February 2022) - Zhang, Maofu; Han, Yanfei; Jia, Chuanbao; Zheng, Zhengang; Li, Haixin; Wu, Chuansong
Abstract: Underwater wet welding plays an important role in marine engineering. The negative influences from the surrounding water inevitably causes unstable processes and weld defects. Underwater submerged arc welding with mixed epoxy resin and flux was proposed to isolate the water and the welding area, and it showed many advantages with highly improved weld quality. However, the ductility and toughness need to be further improved for better performance when serving offshore metal structures. It was proposed that nano Al2 O3 particles were added to the core of flux-cored wire to optimize the solidification processes of the weld pool. The influence of different proportions of nanoparticles on the weld appearance, heat input, inclusions, microstructures, and mechanical properties were investigated. Results shown that the acquired width of coarse-grained heat-affected zone is significantly decreased. With the added Al2 O3 nanoparticles, the solidifying processes of weld pool were significantly changed with increased composite inclusions, refined grain sizes, etc. The average hardness of the weld zone increased. Satisfying elongation and bending performance were achieved when the specific 5% nanoparticles were added in the wire. Graphical abstract: Unlabelled Image